(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article investigates the role and linguistic characteristics of paralinguistic means in intercultural communication within English and Uzbek languages. Paralinguistic elements such as intonation, gestures, facial expressions, pauses, eye contact, and body language significantly influence human interaction and often determine the effectiveness of communication more strongly than words themselves. The study analyzes how cultural values, traditions, mentality, and national communication styles shape the use of non-verbal signals in English and Uzbek societies. Particular attention is paid to the pragmatic and emotional functions of paralinguistic means in spoken discourse. The article also explores how misunderstandings arise in intercultural communication due to differences in non-verbal behavior. Additionally, the importance of paralinguistic competence in language learning, diplomacy, education, media communication, and professional interaction is highlighted. The research demonstrates that successful communication requires not only linguistic knowledge but also awareness of culturally specific paralinguistic norms.